Long-Term Developmental Assessment of Children Recovered from Hypernatremia - Huq, Sayeeda; Sarker, Shafiqul Alam; Jahan, Khursheed; Shaheen, Nazma (Bioresearch Communications, 2023)
Purpose: Imbalances in sodium result in acute neurologic symptoms such as seizures and impaired mental status. Studies investigating the long-term consequences of hypernatremia on cognitive, motor, and language development in children are limited. The aim of this study was to assess the long-term impact of hypernatremia on children’s cognitive, motor, and language development. Methodology:It was an observational study conducted from March 2016 to March 2017 in Dhaka Hospital of icddr,b. In this study,211 children with acute watery diarrhea accompanied with hypernatremia (serum sodium level 150 mmol/L) who had already been enrolled in a previous observational study were prospectively followed for one year.The objective was to investigate if there are any long term neurologic and developmental consequences of hypernatremia in those children. Physical, cognitive, motor, and language development as well as expressive or receptive expression of the children were assessed using a standard tool at the time of discharge (Baseline) and 12 months after discharge (End line). We also assessed IQ in a subgroup of children > 36 months (n=57) using the Wechsler Preschool and Primary Scale of Intelligence in parallel. Results: Among the 211 participants, developmental assessment on motor, cognitive, and language development test was done on 140 (66.3%) children. The mean age of the children at the time of discharge from the hospital (baseline) was 7.9±4.5 months. Compared to mild (serum Na 150 mmol/L to less than 160 mmol/L), and moderately (serum Na 160 mmol/L to 169 mmol/L) hypernatremia, children with severe hypernatremia (serum sodium >170mmol/L) significantly had lower mean scores on the motor, fine motor, and language development score at baseline after adjusting age and weight for the age z score. Although there was an improvement in motor, language, and socioemotional scores, significant improvement was only observed with cognitive function at the end line (p=0.002). In Mmultiple regression after adjusting for potential confounders such as levels of hypernatremia, parents’ education, age of the child, and WAZ, these factors were showed significantly associated with the cognitive function of children. There was no difference in mean IQ level performed at the end-line among the children with different level of hypernatremia (mild, moderate or severe). Conclusion: Children with hypernatremia had poor developmental scores in cognitive, motor, language, and socio-emotional domains at the time of recovery from hypernatremia. However, other than cognitive score, there was no significant improvement in motor or language development at 12 months in children recovering from hypernatremia. Further studies are therefore warranted to reveal any association of motor or language deficit with neurological deficit in those children beyond 12 months. Bioresearch Commu. 10(1): 1386-1392, 2024 (January)